Integration of enteric fever surveillance into the WHO-coordinated Invasive Bacterial-Vaccine Preventable Diseases (IB-VPD) platform: A low cost approach to track an increasingly important disease. - Senjuti Saha; Maksuda Islam; Mohammad J Uddin; Shampa Saha; Rajib C Das; Abdullah H Baqui; Mathuram Santosham; Robert E Black; Stephen P Luby; Samir K Saha (Public Library of Science (PLoS), 2017)
Lack of surveillance systems and accurate data impede evidence-based decisions on treatment and prevention of enteric fever, caused by Salmonella Typhi/Paratyphi. The WHO coordinates a global Invasive Bacterial-Vaccine Preventable Diseases (IB-VPD) surveillance network but does not monitor enteric fever. We evaluated the feasibility and sustainability of integrating enteric fever surveillance into the ongoing IB-VPD platform.The IB-VPD surveillance system uses WHO definitions to enroll 2-59 month children hospitalized with possible pneumonia, sepsis or meningitis. We expanded this surveillance system to additionally capture suspect enteric fever cases during 2012-2016, in two WHO sentinel hospitals of Bangladesh, by adding inclusion criteria of fever ≥102°F for ≥3 days, irrespective of other manifestations. Culture-positive enteric fever cases from in-patient departments (IPD) detected in the hospital laboratories but missed by the expanded surveillance, were also enrolled to assess completion. Costs for this integration were calculated for the additional personnel and resources required.In the IB-VPD surveillance, 5,185 cases were enrolled; 3% (N = 171/5185) were positive for microbiological growth, of which 55% (94/171) were culture-confirmed cases of enteric fever (85 Typhi and 9 Paratyphi A). The added inclusion criteria for enteric fever enrolled an additional 1,699 cases; 22% (358/1699) were positive, of which 85% (349/358) were enteric fever cases (305 Typhi and 44 Paratyphi A). Laboratory surveillance of in-patients of all ages enrolled 311 additional enteric fever cases (263 Typhi and 48 Paratyphi A); 9% (28/311) were 2-59 m and 91% (283/311) >59 m. Altogether, 754 (94+349+311) culture-confirmed enteric fever cases were found, of which 471 were 2-59 m. Of these 471 cases, 94% (443/471) were identified through the hospital surveillances and 6% (28/471) through laboratory results. Twenty-three percent (170/754) of all cases were children <2 years. Additional cost for the integration was USD 44,974/year, a 27% increase to the IB-VPD annual expenditure.In a setting where enteric disease is a substantial public health problem, we could integrate enteric fever surveillance into the standard IB-VPD surveillance platform at a modest cost.